Taxonomic, functional and phylogenetic metacommunity ecology of cladoceran zooplankton along urbanization gradients. Issue 1 (13th April 2017) - Gianuca, Andros T.; Engelen, Jessie; Brans, Kristien I.; Hanashiro, Fabio Toshiro T.; Vanhamel, Matthias; van den Berg, Edwin M.; Souffreau, Caroline; Meester, Luc De
Abstract : As human population size increases and cities become denser, several urban‐related selection pressures increasingly affect species composition in both terrestrial and aquatic habitats. Yet, it is not well known whether and how urbanization influences other facets of biodiversity, such as the functional and evolutionary composition of communities, and at what spatial scale urbanization acts. Here we used a hierarchical sampling design in which urbanization levels were quantified at seven spatial scales (ranging from 50 to 3200 m radii). We found that urbanization gradients are associated with a strong shift in cladoceran zooplankton species traits, which in turn affected phylogenetic composition of the entire metacommunity, but only when considering urbanization at the smallest spatial scale (50 m radius). Specifically, small cladoceran species dominated in more urbanized ponds whereas large‐bodied, strong competitors prevailed in less urbanized systems. We also show that trait and phylogenetic metrics strongly increase the amount of variation in β‐diversity that can be explained by degree of urbanization, environmental and spatial factors. This suggests that the mechanisms shaping β‐diversity in our study system are mediated by traits and phylogenetic relatedness rather than species identities. Our study indicates that accounting for traits and phylogeny in metacommunity analyses helps to explain seemingly idiosyncratic patterns of variation in zooplankton species composition along urbanization gradients. The fact that urbanization acts only at the smallest spatial scale suggests that correctly managing environmental conditions locally has the power to counteract the effects of urbanization on biodiversity patterns. The multidimensional approach we applied here can be applied to other systems and organism groups and seems to be key in understanding how overall biodiversity changes in response to anthropogenic pressures and how this scales up to affect ecosystem functioning.